ChemInform Abstract: Asymmetric Allylation of Sulfonyl Imines Catalyzed by in situ Generated Cu(II) Complexes of Chiral Amino Alcohol Based Schiff Bases. Issue 16 (April 2015) - Ghosh, Debashis; Bera, Prasanta Kumar; Kumar, Manish; Abdi, Sayed H. R.; Khan, Noor‐ul H.; Kureshy, Rukhsana I.; Bajaj, Hari C.
Abstract The enantioselective synthesis of homoallyl amines by Cu(II)‐Schiff base catalyzed reaction of allyltin with aryl or alkenyl‐substituted N‐sulfonylimines is described.